Prognostic Value of Leukocytosis and Lymphopenia for Coronavirus Disease Severity - Glen Huang; Alex J. Kovalic; Christopher J. Graber (Emerging Infectious Diseases, 2020)
To evaluate lymphopenia as a marker for coronavirus disease severity, we conducted a meta-analysis of 10 studies. Severe illness was associated with lower lymphocyte and higher leukocyte counts. Using these markers for early identification of patients with severe disease may help healthcare providers prioritize the need to obtain therapy.